Edukasi gizi sebagai upaya peningkatan pengetahuan dan kesadaran gizi seimbang bagi anak binaan - Bertalina Bertalina; Sutrio Sutrio (JOURNAL of Public Health Concerns, 2026)
Background: Adolescence is a crucial period in the life cycle, marked by rapid growth and development, necessitating a balanced nutritional intake. However, many adolescents still have limited knowledge and awareness regarding the importance of balanced nutrition. This situation also occurs among children in the Special Child Development Institution, who have limited access to health information and nutrition education. Purpose: To increase the knowledge and awareness of children in the care of children regarding the importance of balanced nutrition in maintaining health. Method: This community service activity was conducted on October 23, 2025, at LPKA Class II Bandar Lampung, targeting 39 children aged 14–18. The method used was participatory counseling through interactive lectures, discussions, and demonstrations of healthy menu preparation. Participants' knowledge was measured using pre-test and post-test questionnaires consisting of five questions related to the concept of balanced nutrition and healthy eating patterns. Data were analyzed descriptively to determine changes in participants' knowledge levels. Results: Participant attendance reached 100.0%, with participants participating in all activities until completion. The participation rate was 38.5% actively asking questions, 48.7% less actively asking questions, and 12.8% inactive. There was an increase in knowledge after the educational activity, with 53.8% correctly answering questions, 61.5% understanding the concept of balanced nutrition, 51.3% understanding protein sources, 61.5% understanding the impact of instant noodle consumption, and 61.5% understanding GGL restrictions. In the simulation, most participants were also able to demonstrate complete, accurate, and effective meal planning after the educational activity. Conclusion: Nutrition counseling activities for assisted adolescents using an interactive approach through lectures, discussions, and hands-on practice have proven effective in increasing knowledge and understanding of the concept of balanced nutrition for health. In addition to increased knowledge, participants also demonstrated increased awareness of the importance of a healthy diet, such as reducing consumption of sugary drinks and instant foods and increasing consumption of vegetables and nutritious foods. Most participants were able to apply the concept of balanced nutrition in their menu planning. Suggestion: Nutrition education activities for foster children at Institutions for the Protection of Children need to be carried out continuously to ensure that knowledge and healthy eating behaviors can be maintained and improved. Institutions are expected to support health education activities by providing nutrition information media, such as posters or educational materials, in the foster children's living environments. Keywords: Adolescent nutrition; Balanced nutrition; Foster children; Health promotion; Nutrition education Pendahuluan: Masa remaja merupakan periode penting dalam siklus kehidupan yang ditandai dengan pertumbuhan dan perkembangan pesat sehingga membutuhkan asupan gizi seimbang. Namun, banyak remaja masih memiliki pengetahuan dan kesadaran rendah mengenai pentingnya gizi seimbang. Kondisi ini juga terjadi pada anak binaan di Lembaga Pembinaan Khusus Anak (LPKA) yang memiliki keterbatasan akses terhadap informasi kesehatan dan edukasi gizi. Tujuan: Untuk meningkatkan pengetahuan dan kesadaran anak binaan mengenai pentingnya gizi seimbang dalam menjaga kesehatan. Metode: Kegiatan pengabdian masyarakat ini dilaksanakan pada tanggal 23 Oktober 2025 di LPKA Kelas II Bandar Lampung dengan sasaran 39 anak binaan berusia 14–18 tahun. Metode yang digunakan adalah penyuluhan partisipatif melalui ceramah interaktif, diskusi, dan demonstrasi penyusunan menu sehat. Peningkatan pengetahuan peserta diukur menggunakan kuesioner pre-test dan post-test yang terdiri dari lima pertanyaan terkait konsep gizi seimbang dan pola makan sehat. Data dianalisis secara deskriptif untuk melihat perubahan tingkat pengetahuan peserta. Hasil: Kehadiran peserta mencapai 100.0% dan mengikuti seluruh rangkaian kegiatan hingga selesai, sedangkan tingkat partisipasi peserta sebesar 38.5% aktif bertanya, sebesar 48.7% kurang aktif bertanya dan sebesar 12.8% tidak aktif bertanya. Terdapat peningkatan pengetahuan jumlah peserta setelah kegiatan edukasi dalam menjawab pertanyaan dengan benar sebesar 53.8%, untuk pemahaman konsep gizi seimbang sebesar 61.5%, untuk pengetahuan menyebutkan sumber protein sebesar 51.3%,  untuk pengetahuan dampak konsumsi mie instan sebesar 61.5% dan untuk pengetahuan pembatasan GGL sebesar 61.5%. Dalam simulasi, sebagian besar peserta juga dapat menunjukkan perencanaan menu makanan dengan lengkap, baik dan benar setelah kegiatan edukasi. Simpulan: Kegiatan penyuluhan gizi kepada remaja binaan dengan menggunakan pendekatan interaktif melalui ceramah, diskusi, dan praktik langsung terbukti efektif dalam meningkatkan pengetahuan dan pemahaman mengenai konsep gizi seimbang untuk kesehatan. Selain peningkatan pengetahuan, peserta juga menunjukkan adanya peningkatan kesadaran terhadap pentingnya pola makan sehat, seperti mengurangi konsumsi minuman manis dan makanan instan serta meningkatkan konsumsi sayur dan makanan bergizi, dimana sebagian besar peserta dalam menyusun menu mampu menerapkan konsep gizi seimbang dalam perencanaan menu makanan. Saran: Kegiatan edukasi gizi bagi anak binaan di LPKA perlu dilakukan secara berkelanjutan agar pengetahuan dan perilaku makan sehat dapat terus dipertahankan dan ditingkatkan. Pihak lembaga diharapkan dapat mendukung kegiatan edukasi kesehatan dengan menyediakan media informasi gizi, seperti poster atau materi edukatif di lingkungan tempat tinggal anak binaan.